KARAKTERISTIK FISIK DAN SENSORI TEH CELUP DAUN KERSEN (Muntingia calabura L.) DENGAN PENAMBAHAN BUNGA MELATI (Jasminum sambac L.) DAN KULIT KAYU MANIS (Cinnamomum burmannii) PHYSICOCHEMICAL AND SENSORY CHARACTERISTICS OF KERSEN (Muntingia calabulara L.) TEA BAG WITH THE ADDITION OF JASMINE FLOWER (Jasminum sambac L.) AND CINNAMON SKIN (Cinnamomum burmannii) - Pertiwi, Vera; -, Murhadi; Hidayati, Sri; Sartika, Dewi (Jurusan Teknologi Hasil Pertanian, 2024)
Kersen leaves are a herbal plant that has various health benefits, especially as a medicine for diabetes sufferers. Kersen leaves can be processed into tea bags, but they still have sensory deficiencies in terms of color, aroma and taste. This research aims to determine the effect of adding jasmine flowers and cinnamon and their interaction on the sensory and physical characteristics of kersen leaf tea bags. The method used in this research was a Complete Randomized Block Design (RAKL) with two factors, namely the addition of jasmine flowers which consisted of 3 levels, namely M1 (10%), M2 (20%) and M3 (30%). The second factor, namely the addition of cinnamon powder, consists of 6 levels, namely K0 (0%), K1 (3%), K2 (6%), K3 (9%), K4 (12%) and K5 (15%). The data obtained were analyzed for variance and analyzed further with further Orthogonal Polynomial tests at the 5% and 1% levels. The results of the research showed that the addition of jasmine flowers and cinnamon had a very significant effect on the color, aroma and taste as well as the brightness level of the kersen leaf tea bag. The interaction between the two has a real influence on the color and taste as well as the brightness level of the brew but has no real influence on the aroma of kersen leaf tea bags. Based on research results, kersen leaf tea bags with the addition of jasmine flower concentration of 10% (w/w) and cinnamon concentration of 15% (w/w) produced the best treatment with color value of4.167 (brownish yellow), aroma value of 3.875 (not unpleasant), taste value 4.000 (not bitter), brew brightness level value of 22.850, water content value of 6.9% and ash content value of 5.9%.